Kinetic and technological regularities of the filtration process of suspensions using excipients in the production of baker's yeast. Issue 1 (1st July 2022) - Lavrov, S V; Belozertsev, A S; Barbashin, A M; Nickel, S A; Berestovoy, A A; Dyakova, N A
Abstract: Optimal design and management of baker's yeast production should be based on an in-depth analysis of individual technological processes. Filtration of suspensions using excipients refers to complex technological processes and depends on a large number of factors. In this paper, the kinetic and technological regularities of the process of filtration of suspensions using excipients are considered. The main kinetic regularities of the filtration process are revealed depending on the thickness of the sediment, the pressure drop, concentration, temperature and microbiological purity of the suspension. The effect of the suspension temperature on the main qualitative indicators of yeast: lifting force, acidity and persistence has been established. The performed experimental studies of the filtration process on an industrial continuous vacuum filter and the analysis of the obtained patterns allowed us to formulate a number of recommendations aimed at effective management of the process, reducing losses during the processing of baker's yeast. Recommendations have also been developed to reduce starch consumption and increase the cycle of operation of the vacuum filter.